KAJIAN EKONOMIS RENCANA MODIFIKASI KAPAL TIPELCT UNTUK PENGANGKUTAN MUATAN KONTAINER - Mochammad Haris (2022)
Modification of the LCT 1500 DWT ship into a container ship is one option that can be done because the number of container ships is relatively small. This study aims to provide an economic description of the results of ship activities after modifications have been made. Cost standards are obtained from regulations made by the relevant Ministries and reference costs applied in the field. From the calculation results, it is known that the operational costs that become operating expenses are Rp18,125,457,258,57. It is estimated that in one year the ship will sail 70 times with a load of 38 containers measuring 20 TEU's. The gross profit generated from the activity is Rp34.231.540.000,00. After deducting operating costs, the net profit that can be generated is Rp16.106.082.741,43 or 47,05% of gross profit. Based on the profit generated, the modification of the LCT vessel into a container ship is appropriate to do. Keywords: LCT (Landing Craft Tank), operational costs, gross profit, net profit